Sistem Keamanan IoT dengan Sensor RFID dan Kamera ESP32 untuk Verifikasi Identintas dan Visual - Gunawan, Imam; Hamdi, Khairil; Moko, Joyo Kilat; Sunaryo, Budi (Ikatan Ahli Informatika Indonesia, 2024)
The main problem faced by the madrasah is the lack of visual evidence that can cause a number of problems, including misuse of access cards and the inability to identify perpetrators using fake cards if they want to adopt RFID technology as a security system. This study aims to develop an Internet of Things (IoT)-based security system at Madrasah Ibtidaiyah Wathoniyah Sumber Makmur by utilizing RFID sensors and ESP32 cameras. The system developed is designed to automatically verify identity and provide visual notifications sent via Telegram. The research process began with the collection of qualitative data through direct observation and interviews with the principal, which provided in-depth insights into the existing problems, history, and vision, mission, and organizational structure of the madrasah. Library research was also conducted to collect information from various relevant books and scientific articles, providing the theoretical basis needed for system development. In addition, laboratory research focused on testing and validating prototypes involving hardware components such as ESP32, ESP32 Cam, and PN532 sensors as well as software developed using software such as Arduino IDE, Telegram, and Visual Studio Code. The development method in this study uses a prototyping method that involves active collaboration between designers and end users to ensure that the resulting solution is in accordance with user needs and expectations. The conclusion is that the developed system significantly improves security and access management in madrasahs. This system has proven effective in reducing the risk of access card misuse by providing the necessary visual evidence and accurately detecting illegal access attempts, and can identify perpetrators in illegal access attempts with fake access cards that can be spam.